2017
DOI: 10.3748/wjg.v23.i36.6593
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic perspectives in irritable bowel syndrome: Targeting low-grade inflammation, immuno-neuroendocrine axis, motility, secretion and beyond

Abstract: Irritable bowel syndrome (IBS) is a chronic, recurring, and remitting functional disorder of the gastrointestinal tract characterized by abdominal pain, distention, and changes in bowel habits. Although there are several drugs for IBS, effective and approved treatments for one or more of the symptoms for various IBS subtypes are needed. Improved understanding of pathophysiological mechanisms such as the role of impaired bile acid metabolism, neurohormonal regulation, immune dysfunction, the epithelial barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 233 publications
0
36
0
5
Order By: Relevance
“…Low‐grade inflammation plays a vital role in IBS pathogenesis . In particular, an increased number of mast cells and a higher degree of mast cell activation have been reported in biopsies of IBS patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐grade inflammation plays a vital role in IBS pathogenesis . In particular, an increased number of mast cells and a higher degree of mast cell activation have been reported in biopsies of IBS patients .…”
Section: Resultsmentioning
confidence: 99%
“…Low-grade inflammation plays a vital role in IBS pathogenesis. 38 In particular, an increased number of mast cells and a higher degree of mast cell activation have been reported in biopsies of IBS patients. 12,13 No morphological changes in the colon of MS rats were noted compared with the control group ( Figure 5A), and MS did not increase myeloperoxidase activity in the colon ( Figure 5B).…”
Section: Metformin Inhibits Colonic Low-grade Inflammation In Ms Ratsmentioning
confidence: 99%
“…In all IBS patients, the serum PRDX1 (r = .335, P < .001) and TNF-α 16,33,[35][36][37] PRDX1 is associated with some tumors [21][22][23]38 and especially associated with colorectal cancer caused by chronic inflammation. 39,40 However, few studies have examined the relationship between PRDX1 and intestinal inflammation.…”
Section: Correlation Of Ibs-sss With Prdx1 and Tnf-α In Patients Wimentioning
confidence: 99%
“…Although no studies have yet evaluated the efficacy of prucalopride in IBS-C (ref. 88 ). Renzapride is a full agonist for the 5HT type 4 receptor and an antagonist to 5HT type 2b and 5HT type 3 receptors.…”
Section: Serotonin Receptor Agonists and Antagonistsmentioning
confidence: 99%
“…Renzapride is a full agonist for the 5HT type 4 receptor and an antagonist to 5HT type 2b and 5HT type 3 receptors. Studies have shown that Renzapride is not superior to placebo in relieving IBS symptoms 88 .…”
Section: Serotonin Receptor Agonists and Antagonistsmentioning
confidence: 99%